Effect of osmotic dehydration on kiwifruit: Results of a multianalytical approach to structural study - Dalla Rosa, Marco (2011)
This paper presents the results of the comparison of different analytical techniques (Differential Scanning Calorimetry - DSC, Low Field Nuclear Magnetic Resonance - LF-NMR, Light Microscopy - LM and Transmission Electron Microscopy – TEM) in order to evaluate the mass transfer, water status and cellular compartment modifications of the kiwifruit outer pericarp tissue during osmotic dehydration treatment (OD). Two kiwifruit species, A. deliciosa and A. chinensis were submitted to OD. OD was performed in a 61.5 % w/v sucrose solution at three different temperatures (25, 35 and 45 °C), with treatment time from 0 to 300 min. Peleg’s model highlighted that the main response differences between the two kiwifruit species occurred during the initial phase of the osmotic treatment. DSC parameters appeared to be sensitive to water and solid exchange between fruits and osmotic solution. LF-NMR proton T2 revealed the consequences of the water-solid exchange on the cell compartments, namely vacuole, cytoplasm plus extracellular space and cell wall. During OD, the reduction of the vacuole proton pool, detected by LF-NMR, suggested a shrinkage of such compartment, confirmed by LM. Cell walls of outer pericarp showed considerable changes in size, structure and stain uptake during OD observed at TEM. The proposed multianalytical approaches should enable better design of combined processing technologies permitting the evaluation of their effects on tissue response.